2017
DOI: 10.1103/physreva.96.053606
|View full text |Cite
|
Sign up to set email alerts
|

Tunable axial potentials for atom-chip waveguides

Abstract: We present a method for generating precise, dynamically tunable magnetic potentials that can be described by a polynomial series along the axis of a cold-atom waveguide near the surface of an atom chip. With a single chip design consisting of several wire pairs, various axial potentials can be created by changing the ratio of the currents in the wires, including double wells, triple wells, and pure harmonic traps with suppression of higher-order terms. We use this method to design and fabricate a chip with mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
(120 reference statements)
0
14
0
Order By: Relevance
“…The new atom chip experiments are described in Ref. [8]. These experiments do not require BEC but rather atoms evaporatively cooled to 1 − 4 µK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The new atom chip experiments are described in Ref. [8]. These experiments do not require BEC but rather atoms evaporatively cooled to 1 − 4 µK.…”
Section: Resultsmentioning
confidence: 99%
“…b.) The top layer (black) of the cross wire trap chip consists of wire pairs used to make a controllable polynomial magnetic potential [8]. The wire pattern on the front side of the chip (dark gray) was used for making a four wire waveguide.…”
Section: Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the prescription of [19], we assume that the potential is separable, i.e., V(r r r) = V(x) + V ⊥ (r ⊥ ), and the k-vectors of the laser beams point in the x-direction. Collisions are neglected as we have previously analyzed the effects of collisions in a similar interferometer and do not expect atom-atom collisions to have a significant impact on the results [20].…”
Section: The Modelmentioning
confidence: 99%
“…Recent research has demonstrated a high degree of control over the residual field [19]. Here, we analyze the effect of a controlled residual potential in a Talbot-Lau interferometer with a gas of cold, thermal atoms using a Wigner function approach.…”
Section: Introductionmentioning
confidence: 99%